2019
DOI: 10.1038/s41598-019-39153-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol predicts migration timing and success in both Atlantic salmon and sea trout kelts

Abstract: Kelts – individuals of anadromous fish species which have successfully spawned and may return to sea to repeat the cycle – are perhaps the least studied life stage of iteroparous fish species. To date, our understanding of what makes them successful in their return migration to sea is limited. We investigated the relationship between three physiological parameters (baseline cortisol, baseline glucose and low molecular weight antioxidants) and the timing and success of Atlantic salmon (Salmo salar) and sea trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…Although the majority of kelts with low body condition initiated downstream migration in the autumn, in contrast with previous studies (i.e. Halttunen et al, 2013; Birnie-Gauvin et al, 2019), no kelts from our study entered the sea before spring and instead decided to overwinter in the lower section of the Middle River or near its mouth. Complementary to our findings on the condition-dependent downstream migration timing of kelts, nutritional status was also linked to overwinter riverine survival, so that the survival probability of 2SW kelts decreased with decreasing post-spawning triglyceride concentration (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the majority of kelts with low body condition initiated downstream migration in the autumn, in contrast with previous studies (i.e. Halttunen et al, 2013; Birnie-Gauvin et al, 2019), no kelts from our study entered the sea before spring and instead decided to overwinter in the lower section of the Middle River or near its mouth. Complementary to our findings on the condition-dependent downstream migration timing of kelts, nutritional status was also linked to overwinter riverine survival, so that the survival probability of 2SW kelts decreased with decreasing post-spawning triglyceride concentration (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar condition-dependent migration timing of Atlantic salmon kelts, with depleted individuals initiating downstream movement soon after spawning, was previously described by Halttunen et al (2013). In addition to a lower body condition factor in autumn migrating Atlantic salmon kelts (Halttunen et al, 2013), Birnie-Gauvin et al (2019) reported that early migrants tended to have higher baseline plasma cortisol levels compared to spring migrating kelts. This might suggest that kelts perceive low nutritional state and low resource availability as a stressful stimuli, which might trigger the upregulation of cortisol levels for feeding and preparation for salt water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birnie‐Gauvin et al . () also found baseline cortisol to be associated with the migration timing and success of anadromous S. trutta kelts. Birnie‐Gauvin et al .…”
Section: Genetic and Environmental Determinants Of Facultative Migrationmentioning
confidence: 85%
“…state and that internal state can in turn influence migration. For example, recent evidence suggests that stress levels and nutritional status can both impact migration distance and success in salmonids (Bordeleau et al, 2018;Birnie-Gauvin et al, 2019a). Few such studies exist, but these can shed light on the mechanistic links between internal state and migratory behavior.…”
Section: Internal Statementioning
confidence: 99%